Prolonged Conservative Management vs. Early Surgery in Symptomatic Lumbar Disc Herniation: A Retrospective Descriptive Study from a Tertiary Spine Center in Nepal - Dahal, Ram Krishna; Bijukachhe, Binod; Shrestha, Aayush; Dumre, Arjun; Neupane, Sohil; Khanal, Prajwal; Baral, Biraj; Pandey, Asim (Grande Medical Journal, 2025)
Background Lumbar disc herniation is a leading cause of low back and radicular pain, often impairing daily function and quality of life. Lumbar discectomy is a commonly performed procedure worldwide, especially in patients with severe or persistent symptoms. However, its long-term superiority over conservative treatment remains a matter of debate. This study aims to describe the clinical outcomes of patients treated conservatively and surgically at a high-volume spine center in Nepal. Method This retrospective observational study included 8,231 patients with symptomatic LDH who presented to the spine outpatient department of Grande International Hospital from 2018 to 2024. Patients were managed either conservatively or surgically. VAS and ODI scores were assessed at 6 weeks, 3 months, and 1 year for both groups. Result A total of 8,231 patients meeting the eligibility criteria were included. Of these, 196 (2.4%) required surgical decompression, while 8,035 (97.6%) were managed non-operatively. At 6 weeks, VAS scores improved from 8.2 to 4.6 in the surgical group, compared to 6.5 from 8.2 in the non-operative group. By 1 year, VAS scores further decreased to 2.3 in the surgical group and 2.2 in the non-operative group. Similarly, ODI scores at 1 year declined to 27 for both surgical patients and those managed non-operatively. Conclusion Surgical treatment showed faster initial improvement, but long-term outcomes were comparable. While early surgery provides faster symptom relief, long-term outcomes between the two approaches are comparable. These findings highlight the importance of individualized treatment decisions rather than defaulting to conservative therapy for all patients for prolonged period of time.